A non-randomized feasibility study of a voice assistant for parents to support their children’s mental health - Richmond, Sally; Bell, Mietta; Ngo, Dyung; Yap, Marie B. H. (Frontiers in Psychology, 2024)
Background Mental disorders affect one in seven Australian children and although effective, evidenced based treatments exist, there is a critical shortage of mental health clinicians which has created a “treatment gap.” Artificial intelligence has the potential to address the high prevalence rates of mental disorders within overburdened mental health systems. Methods This was a non-randomized feasibility study to evaluate the novel application of voice technology to an evidence-based parenting intervention designed to support children’s mental health. We deployed an Amazon Alexa app to parents recruited from the community (N = 55) and to parents with children receiving psychological treatment (N = 4). Parents from the community used the app independently whereas parents from the clinical group used the app in conjunction with attending a six-week parenting program. The primary outcome measure, feasibility was assessed in terms of acceptability, via recruitment and retention rates, quantitative surveys and qualitative interviews. Results In the community group, the recruitment rate was 23.8% and the retention rate 49.1%. In the clinical group, all 6 families approached for recruitment agreed to participate and 4 out of 6 completed the trial. Parents attending the parenting program spent on average, three times longer using the app than parents from the community. Overall, parents reported that the app contained easy-to-understand information on parenting, and that they could see the potential of voice technology to learn and practice parenting skills. Parents also faced several challenges, including difficulties with installation and interactions with the app and expressed privacy concerns related to voice technology. Further, parents reported that the voices used within the app sounded monotone and robotic. Conclusion We offer specific recommendations that could foster a better voice assistant user experience for parents to support their children’s mental health. The app is highly scalable and has the potential to addresses many of the barriers faced by parents who attempt to access traditional parenting interventions.